DETERMINAN BRAND LOYALTY - Puspaningrum, Astrid (Jurnal Aplikasi Manajemen, 2018)
The purpose of this study is to analyze the influence of brand awareness and brand associations on brand loyalty. The population of this research is Population in this research is a consumer who shops at hypermarket existing Malang City, which is Carrefour, Giant, and Matahari with sample counted 50 responders. Data analysis in this research used multiple regression. The results show that brand awareness and brand associations affect brand loyalty. In order to increase customer to loyal to hypermarket then management needs to increase awareness and brand association by way of self-expression through promotion and event marketing activity, to create an emotional bond with a brand